Combined thoracoscopic and laparoscopic surgery for epiphrenic diverticulum with associated gastroesophageal reflux disease: a case report - Yusuke Uchi; Soji Ozawa; Tomofumi Ando; Koki Hayashi; Takuma Aoki; Motohide Shimazu (Surgical Case Reports)
Abstract Background Surgery is indicated for symptomatic epiphrenic esophageal diverticula. Based on the features of a case, thoracoscopic or laparoscopic approaches may be used. Epiphrenic diverticula are often associated with esophageal motility disorders, but cases of reflux esophagitis have rarely been reported. In this report, we describe a case of an epiphrenic esophageal diverticulum with reflux esophagitis, which was successfully treated by thoracoscopic diverticulectomy and laparoscopic fundoplication. Case presentation A 69-year-old man visited the hospital with a chief complaint of eructation and hiccup. Upper gastrointestinal endoscopy revealed a diverticulum in the left wall of the esophagus, which was 37–45 cm distal to the incisors. High-resolution manometry (HRM) showed no esophageal motility disorders. Due to the large size of the diverticulum, a thoracoscopic resection of the esophageal diverticulum was performed. Additionally, the patient had reflux esophagitis due to a hiatal hernia. The anti-reflux mechanism would be more impaired during the diverticulectomy; therefore, we decided that anti-reflux surgery should be performed simultaneously. Thoracoscopic esophageal diverticulectomy and laparoscopic Dor fundoplication were performed. The patient had an uncomplicated postoperative course and was discharged on the tenth operative day. He has been symptom-free without acid secretion inhibitors for 21 months after the surgery. Conclusions We described a rare case of a large epiphrenic diverticulum with reflux esophagitis. A good surgical outcome was achieved by thoracoscopic resection of the diverticulum and laparoscopic Dor fundoplication.